“Obesity paradoxes”: main causes of an “inverse” cardiovascular epidemiology - M. A. Druzhilov; Т. Yu. Kuznetsova; О. Yu. Druzhilova (Кардиоваскулярная терапия и профилактика)
Taken the continuous increase of obesity prevalence, most countries in the world deal with an epidemy, one of the main healthcare concerns. In the structure of nosology associated with overweight and obesity, cardiovascular is leading. Also, in the recent trials and meta analyses there is negative correlation found for body mass index and clinical outcomes characterizing better survival and lower events rate in those with higher BMI, as less chronic diseases. Such facts facilitated a number of discussions on the predictive value of overweight and obesity and consideration whether to correct those in cardiovascular patients as secondary prevention. Current article is focused on the main causes for an “inverse” cardiovascular epidemiology in overweight and obesity.